Optimization of tool life in miling - Mohd Ezuwanizam, Masral (2010)
This paper discuss of the Optimization of Tool Life in Milling. The objective of the paper is to obtain an optimal setting of turning process parameters –cutting speed, feed and depth of cut, which may result in optimizing tool life of TiN coated carbide inserts while milling aluminium 6061. Data is collected from FANUC Robodrill CNC milling machines were run by 15 samples of experiments. A dimensional-accuracy model for the end milling of aluminum alloys under dry conditions is presented. To build the quadratic model and minimize the number of experiments for the design parameters, response surface methodology (RSM) with a Box-Behnkin method is used to design the table in MINITAB packages. The inputs of the model consist of feed, cutting speed and depth of cut while the output from the model is tool life and tool wear was measured using Image Analyzer microscope.The model is validated through a comparison of the experimental values with their predicted counterparts. A good agreement is found where from the RSM approaches which reliable to be use in tool wear prediction. The direct and interaction effect of the machining parameter with tool wear were analyzed and plotted, which helped to select process parameter in order to reduce tool wear which ensures quality of milling. It is shown that the tool wear in end milling decreases with the increase in feed, radial depths of cut and cutting. From the experiment it is found that the effect of axial depth of cut on tool life is not so significant. The speed effect is dominant followed by the feed and the axial depth of cut. For end-milling of aluminium alloy 6061, the optimum condition that is required to maximize the coated carbide tool life are as follow: cutting speed of 180m/min, federate of 0.2 mm/rev, axial depth of 1.5 mm.